UPAYA GURU PENDIDIKAN AGAMA ISLAM (PAI) DALAM MENCIPTAKAN KOMUNITAS BELAJAR DI SMKN 1 MANDAU - Jon Helmi (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2018)
The purpose of this study was to find out Islamic education teachers’ efforts in creating learning communities in SMKN 1 (vocational school) mandau. The sample of the study was 30 Islamic education teachers. This study belongs to qualitative descriptive. The sources of the data were primary and secondary. To collect the data, the writer used several techniques such as observation, questionnaires, and interviews. After the data were collected, it then analyzed from its qualitative to quantitative. The data was analyzed descriptively. The results of the study showed that the efforts made by the teachers in creating a learning community can influence the enthusiasm for learning, and improve the existing learning system; it provided free time for students who have not yet finished their learning to have an increased ability than before (467 or 11.67%). Similarly, the highest option was “A” means that it was very often. It indicated that Islamic Education Teachers created maximum results of creating learning communities; this could be shown from several changes in student learning methods, student outcomes, and the formation of positive learning communities for vocational students who are initially less enthusiastic about following normative adaptive lessons and prefer productive lessons.